Long-term scheduling of cleaning of heat exchanger networks: comparison of outer approximation-based solutions with a backtracking threshold accepting algorithm - Smaili, F; Vassiliadis, V S; Wilson, D I (Chemical engineering research & design, 2002)
Part of a special topic section on techno-economic analysis containing 4 other papers. Management of the cleaning of heat exchanger networks (HENs) subject to significant fouling plays an important role in oil refinery heat recovery economics. This work explores the options offered by stochastic optimisation techniques for combinatorial problems applied to the HEN cleaning problem and scheduling of actions. In particular, a backtracking threshold accepting algorithm (BTA) is developed, derived from methods typified by simulated annealing, and compared to a commercial outer approximation (OA) based formulation. 2 large-scale case studies are described which conclude that the BTA approach is able to handle larger problems than the OA solver used.